Pengaruh Ekstensifikasi Pajak, Pemeriksaan Pajak, Penagihan Pajak, Kepatuhan Wajib Pajak dan Intensifikasi Pajak Terhadap Penerimaan Pajak (Study Empiris pada KPP Pekanbaru Tampan) - Risky, Cindi Amelia; Silfi, Alfiati; Wiguna, Meilda (SYNERGY: Jurnal Bisnis dan Manajemen, 2023)
This study aims to examine the effect of tax extensification, tax audit, tax collection, taxpayer compliance and tax intensification on tax revenue at KPP Pratama Pekanbaru Tampan. The population of this study included all employees of KPP Pratama Pekanbaru, totaling 75 people. The data used is primary data with questionnaire data sources. Data analysis used in this study uses a multiple linear regression analysis model where tax extensification, tax inspection, tax collection, taxpayer compliance and tax intensification are the independent variables and tax revenue is the dependent variable. The hypothesis test used is the partial test or t test. The results of this study conclude that tax extensification, tax audit, tax collection, taxpayer compliance have an effect on tax revenue, while tax intensification has no effect on tax revenue.The Adjusted R2results of the five independent variables on the dependent variables have an effect of 73.6%,while the remaining 26,4% are influenced by variables outside the research model.